Editorial - J. Rossouw (Acta Theologica)
From text: The first edition of what turned out to be one of the foundational texts of what became known as the intellectual movement of Radical Orthodoxy (RO), John Milbank’s Theology and social theory: Beyond secular reason was published in 1990. Something of this seminal book’s impact is conveyed in the two blurbs on the back cover of the second edition, published in 2006. According to Stanley Hauerwas, the book “has proven to be a bombshell”, while Charles Taylor writes that when “the first edition was published, the reaction was one of shock”. Why was this so?